2021
DOI: 10.1039/d1em00273b
|View full text |Cite
|
Sign up to set email alerts
|

Fluorophores in surface freshwaters: importance, likely structures, and possible impacts of climate change

Abstract: Fluorescence spectroscopy is one of the most useful techniques that are currently available for the characterisation of organic matter in natural water samples, because it combines easy availability of instrumentation,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 112 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…Over the past two decades, numerous studies have suggested that humic-like and protein-like fluorescence can serve as proxies for lignin and amino acid concentrations in DOM. , The protein-like fluorescence in DOM is primarily derived from aromatic amino acids, such as Tyr and Trp, in aquatic environments. Our results demonstrated that the reaction of Trp and Tyr with 3 C* generates LLPO, which can directly oxidize R-PhOH and CDOM-related reductants.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, numerous studies have suggested that humic-like and protein-like fluorescence can serve as proxies for lignin and amino acid concentrations in DOM. , The protein-like fluorescence in DOM is primarily derived from aromatic amino acids, such as Tyr and Trp, in aquatic environments. Our results demonstrated that the reaction of Trp and Tyr with 3 C* generates LLPO, which can directly oxidize R-PhOH and CDOM-related reductants.…”
Section: Discussionmentioning
confidence: 99%
“…From a mechanistic point of view, this photochemical process could involve dimerisation/oligomerisation, as well as hydroxylation of the precursor molecules (see Scheme S1 in the Supplementary Material, hereinafter SM, for a possible example of such processes) (De Laurentiis et al, 2013;Hoffer et al, 2004;Mabato et al, 2022). Indeed, evidence suggests that phenolic oligomers and polyhydroxylated aromatic compounds are reasonable humic fluorophores (Vione et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Excitation-emission matrix (EEM) fluorescence spectroscopy is one of the most straightforward ways to characterise organic matter in natural water samples (Minor et al, 2014;Stedmon et al, 2003). The signals that are most often detected in EEM spectra are those of proteins and HS (Vione et al, 2021). Protein fluorescence is detected based on the main fluorophores, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence excitation emission matrix (EEM) spectroscopy has found many applications in the analysis of, for example, food samples, machinery fluids, , environmental samples , such as water and soil, , and even neutrino scintillator liquids . EEM spectroscopy is usually performed by scanning a light sourceusually a broadband lamp coupled to a monochromatorand collecting the fluorescence using either an array detector or a second monochromator and broadband detector.…”
Section: Introductionmentioning
confidence: 99%